Biocontrol for Shrimp Disease: Comprehensive Review and a Bacterial Disease Biocontrol Practice - Xinyi He; Jian He; Minghong Liu; Menghuang Xu; Jianjun Jiang; Minze Liao; Chengcheng Wu; Peiyun Han; Long Zhang; Shaoping Weng; Zhixun Guo; Jianguo He (Reviews in Aquaculture, 2026)
Biocontrol is a key strategy for disease control, as it is environmentally friendly and widely applicable. This review elaborates on biocontrol in aquaculture, particularly in shrimp culture. Biocontrol in shrimp culture mainly relies on four strategies: (i) direct kill pathogen by Bdellovibrio or bacteriophages; (ii) suppression of intestinal pathogens with probiotics; (iii) reduction of environmental pathogens via probiotics, biofloc, or bivalves and fish; and (iv) blocking transmission of pathogens using predatory fish. “Shrimp‐fish polyculture” system for diseased biocontrol, which is convenient, effective, and affordable, focuses on blocking disease transmission routes. The efficacy of this strategy has been firmly established for white spot syndrome virus (WSSV). However, its application to other shrimp diseases is not widespread. Herein, a “shrimp‐fish polyculture” biocontrol plan was designed and successfully validated against Vibrio harveyi in shrimp. These findings successfully expand the application of the “shrimp‐fish polyculture” system to the control of bacterial diseases in shrimp, thereby offering new perspectives and methods for the biocontrol of diseases caused by various shrimp pathogens.